2016
DOI: 10.1093/ecco-jcc/jjw194
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Phenotype at Diagnosis of Very-early-onset Compared with Later-onset Paediatric Inflammatory Bowel Disease: A Population-based Study [1988–2011]

Abstract: Background and Aims: Very-early-onset inflammatory bowel disease [VEO-IBD] is a form of IBD that is distinct from that of children with an older onset. We compared changes over time in the incidence and phenotype at diagnosis between two groups according to age at IBD diagnosis: VEO-IBD diagnosed before the age of 6 years, and early-onset IBD [EO-IBD] ]. Rectal bleeding and mucous stools were more common in patients with VEO-IBD, whereas weight loss and abdominal pain were more frequent in those with EO-IBD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
73
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 45 publications
(61 reference statements)
12
73
1
1
Order By: Relevance
“…However, we found no gender difference among patients with EO‐CD. The prevalence of EO‐CD in our cohort was 49.6%, which is higher than western European studies . Among patients with EO‐CD, 61.8% were diagnosed at an age of <6 years (VEO‐CD); while current researches have suggested that 9.9% to 33% of the patients with EO‐IBD were diagnosed before the age of 6 years .…”
Section: Discussioncontrasting
confidence: 65%
“…However, we found no gender difference among patients with EO‐CD. The prevalence of EO‐CD in our cohort was 49.6%, which is higher than western European studies . Among patients with EO‐CD, 61.8% were diagnosed at an age of <6 years (VEO‐CD); while current researches have suggested that 9.9% to 33% of the patients with EO‐IBD were diagnosed before the age of 6 years .…”
Section: Discussioncontrasting
confidence: 65%
“…Colitis, including ulcerative colitis and Crohn's disease, is an inflammatory bowel disease (IBD) with unknown etiology . IBD has a high incidence that affects millions of people globally and the prevalence increases annually . There are many factors thought to lead to the development of colitis, such as age, environment, gender, genetics, and diet .…”
Section: Introductionmentioning
confidence: 99%
“…The Paris classification did not formally separate “very early onset” disease but the emergence of a subgroup of children younger than 2 years at diagnosis has highlighted the increased likelihood of hereditable disease and the need to consider screening for a monogenic disorder in these children although incidence in this group is static …”
mentioning
confidence: 99%